2012
DOI: 10.1017/s0266467412000612
|View full text |Cite
|
Sign up to set email alerts
|

Remote video-camera traps measure habitat use and competitive exclusion among sympatric chimpanzee, gorilla and elephant in Loango National Park, Gabon

Abstract: Abstract:Species commonly exist in sympatry, yet ecological studies are often based on a single species approach while ignoring the impact of sympatric competitors. Over 13 mo we used 24 remote video-camera traps to monitor habitat use of sympatric chimpanzee, gorilla and elephant in four different habitat types in Loango National Park, Gabon. Habitat use by each species was predicted to vary according to seasonal changes in food availability and precipitation. Increased interspecific competition between the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 30 publications
2
67
0
3
Order By: Relevance
“…It has great potential to provide unique and valuable data on the impacts of conservation threats [71], sociodemographics [23], behavioural plasticity [32,55,3], disease mapping and screening [9], species interactions [23], habitat use [53,24], feeding ecology [24,51,59], activity patterns [32,55], and ranging patterns [48].…”
Section: Monitoring In Ecology Todaymentioning
confidence: 99%
See 1 more Smart Citation
“…It has great potential to provide unique and valuable data on the impacts of conservation threats [71], sociodemographics [23], behavioural plasticity [32,55,3], disease mapping and screening [9], species interactions [23], habitat use [53,24], feeding ecology [24,51,59], activity patterns [32,55], and ranging patterns [48].…”
Section: Monitoring In Ecology Todaymentioning
confidence: 99%
“…The long-term data on the demographics and group structure of dozens of known gorilla units from Mbeli Bai could form a unique and novel combination with spatially-explicit capture-recapture data that, when combined, could tackle a myriad of socioecological questions (e.g. ranging patterns, habitat use, seasonal activity patterns, disease screening) as well as population estimates for the wider area, potentially at a park-wide or landscape level [35,53,23,24].…”
Section: New Research Horizonsmentioning
confidence: 99%
“…1). Camera traps can record presence/absence of a rare or elusive species (Bezerra et al 2014;Gerber et al 2014), establish habitat requirements (Head et al 2012;Numata et al 2005), and document geographical range (Easton et al 2011). To optimize the likelihood of capturing the focal subject, researchers have used lures (Bezerra et al 2014;Kierulff et al 2004), strategically placed camera traps near critical resources, such as natural canopy bridges (Gregory et al 2013), bamboo zones (Easton et al 2011), and natural licks (Lhota et al 2012).…”
Section: Camera Trap Applicationsmentioning
confidence: 99%
“…Studies focusing on the consumption of masting fruit resources (Miura et al 1997;Prasad et al 2010), seed dispersal (Miura et al 1997), and of primates dropping or knocking off fruits that terrestrial animals then eat (Prasad et al 2010), have informed researchers on how primates contribute to forest ecology. Moreover, video camera trapping showed that seasonal fruit abundance may influence interspecific competition between common chimpanzees (Pan troglodytes troglodytes), gorillas (Gorilla gorilla gorilla), and forest elephants (Loxodonta cyclotis) (Head et al 2012). Camera trap research on habitat use patterns by sympatric chimpanzees and gorillas reflect the species' dietary preferences, in that chimpanzees are frugivorous and prefer montane forests and gorillas are folivores and are distributed across habitat types (Nakashima et al 2013).…”
Section: Recording Primate Behaviormentioning
confidence: 99%
“…Recently, some studies have been using camera-traps for a various purpose, e.g. making a species list of large ground-dwelling mammals (Treves et al 2010); monitoring animals visiting "bai" (large forest clearings with mineral-rich soil and water) (Gessner et al 2014); estimating the relative and absolute abundance of animals such as leopards (Henschel et al 2011), or great apes and elephants (Head et al 2012, Nakashima et al 2013b; detecting rare monkeys (Coad et al 2010, Easton et al 2011 or golden cats (Aronsen 2010); monitoring die-off of large ungulates (Elkan et al 2009); and identifying seed disperser/predators (Babweteera et al 2007, Nyiramana et al 2011, Beaune et al 2012, Moupela et al 2013. Given that a lot of limitations have not been solved in conventional methods including direct sightings (e.g.…”
Section: Introductionmentioning
confidence: 99%